THE PROGRESSIVE METHOD – GENETICS: A Model in the Tasks of Old Testament Theology - Agustina Pasang; Sutay Wirawan; Linda Irene Sinaga; Ronny Ronald Simamora (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
The purpose of this article is to discover the use of the progressive-genetic method in the task of Old Testament Theology. This method is understood as the exposition or explanation of God’s Revelation as presented by the Bible, more specifically in the sense that Devine Revelation is centered on some covenant made by God with Noah, Abraham, Moses, and through Christ which all shows the organic existence of the Bible and biblical anatomy. In conclusion, in carrying out the task of Old Testament Theology, genetically progressive methodology can be used as a model in addition to other methodologies, which reveal God’s ever-evolving Revelation as revealed in the Bible that God gave or revealed to certain people named specifically by God self.